Answer: see Explanation
Step-by-step explanation:
THE GAINEY'S:
Recursive Formula :
A1 = $10
An = An-1 + $10
A2 = $10 + $10 = $20
Where n = day of the month
Explicit formula :
y = a + b(c - 1)
WHERE:
y = final amount
initial amount = a
Increment on initial amount = b
Day of the month = c
THE ARNOLD'S :
Recursive formula:
First day of the month (A1) = $10
An = 2(An-1)
A2 = 2(A1) = 2(10) = $20
A3 = 2(A2) = 2(20) =$40
Explicit formula:
y = a(b)^c
Where :
y = final amount
initial amount = a
Increment on initial amount = b
Day of the month = c